EUROPEAN EXPERIENCE OF PUBLIC ADMINISTRATION IN ENSURING THE FINANCIAL SECURITY OF THE STATE - Shtantsel, Serhii (Public Management and Policy, 2025)
The article examines the current system of public administration of the EU in the financial sphere in the language of modern challenges and threats. The relevance of the study is due to the need to adapt the financial management of Ukraine to the European system of financial security management. The aim is to study the European practice of public administration in the field of ensuring financial security. The study is aimed at identifying the features of financial regulation in the EU according to the components of financial security, trends in public administration in the financial sphere. The study used such methods as analysis, statistical review of revenues and expenditures of the EU budget in 2014–2023. The method of analyzing the formation of a new system of public administration in the financial sphere of the EU allowed to identify approaches to financial management that should be implemented today in Ukraine. The results of the study showed that after the financial crisis, a new institutional structure of public administration in the field of ensuring financial security was created in the EU with the distribution of management functions by areas of influence and regulation. The purpose of management activities is focused on achieving financial stability and sustainability of financing, digital transformation, and convergence of supervision of the EU financial system. EU financial regulators operate on the basis of cooperation, coordination of efforts and measures, and also interact with national regulators to assess the compliance of their decisions with national financial sector regulation policies. Financial planning in the EU is based on the Financial Regulation, the main purpose of which is to ensure the settlement of issues of using the EU budget in the medium term. For financial planning of long-term revenues and expenditures, the Multiannual Financial Framework is used, the changes to which are related to the challenges of the external environment. In response to the war, recovery instruments were introduced, coverage of loans of EU Member States from the budget was expanded, and loans were included in the EU budget as part of macro-financial assistance to Ukraine. In addition, the modernization of the EU budget structure provided for the development of new programs, recovery instruments and strengthening of resilience to strengthen financial stability. The conclusions established that improving the public administration system in the field of financial security is extremely important in the context of maintaining financial stability. At the same time, a key aspect that should be taken into account in financial regulation is the specifics of modern challenges. Future research should be aimed at studying the main indicators of ensuring financial security and stability in the EU, as a result of the development of public administration financial institutions in this area.